2019
DOI: 10.12669/pjms.36.1.1144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endoscopic variceal band ligation sessions in obliteration of esophageal varices

Abstract: Objective: To determine number of sessions of Endoscopic variceal band ligation required to obliterate the esophageal varices. Methods: This study was conducted at Civil Hospital Karachi between June 2018 to April 2019. All patients undergoing endoscopic Variceal Band Ligation (EVBL) were inducted. Number of sessions of band ligation required to obliterate the varices were recorded. Number of EVBL sessions were correlated with Child-Pugh’s Score and etiology of CLD by χ2 test, while it was compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The study stressed the need for screening oesophagogastroduodenoscopy (OGD) to look for oesophageal varices (OV) prior to starting sorafenib and suggested the importance of achieving good OV obliteration before treatment initiation [7]. However, endoscopy is an invasive procedure that comes with risks and may not be preferred especially in patients who may already be frail from an advanced malignancy [8,9]. With the ongoing COVID-19 pandemic, many elective procedures may have been canceled or delayed, which may lead to further postponement in treatment initiation.…”
Section: Introductionmentioning
confidence: 99%
“…The study stressed the need for screening oesophagogastroduodenoscopy (OGD) to look for oesophageal varices (OV) prior to starting sorafenib and suggested the importance of achieving good OV obliteration before treatment initiation [7]. However, endoscopy is an invasive procedure that comes with risks and may not be preferred especially in patients who may already be frail from an advanced malignancy [8,9]. With the ongoing COVID-19 pandemic, many elective procedures may have been canceled or delayed, which may lead to further postponement in treatment initiation.…”
Section: Introductionmentioning
confidence: 99%
“…EBL is a simple, safe, and effective method that is commonly used for the treatment of EV. [17,18] Endoscopic ligation of GV was first reported in the early 1990s [19][20][21] ; however, this method has not been widely accepted because of limitations in the devices used for ligation and because the indications for GV ligation are greatly limited. [20][21][22][23][24][25] Moreover, in previous studies, it was found that detachable snares and nylon loops could only be used to ligate protuberant nodular or tuberous GV, whereas band ligators could only be used to ligate small-to moderate-sized GV due to their small volume.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that varices are found in around 70% of Child-Turcotte-Pugh (CTP) class B or C patients, and in 40% of CTP class A patients. 4,5 Bearing in mind the above mentioned figures, it is evident that a significant proportion of patients with a newly diagnosed early cirrhosis undergo endoscopy needlessly. This concept became even more crucial in recent years, when cirrhosis is diagnosed earlier because of the availability of non-invasive methods for its diagnosis such as Liver Stiffness Measurement (LSM) by Fibroscan or Elastography.…”
Section: Introductionmentioning
confidence: 99%